2018
DOI: 10.1017/s1474747218000276
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of financial education on financial literacy: evidence from a sample of college students

Abstract: Based on a sample of university students, we provide evidence that a small-scale training intervention has both a statistically and economically significant effect on subjective and objective assessments of financial knowledge. We also show that the intervention increases self-assessed more than actual financial knowledge. The intervention consists of measuring financial literacy before and after a small on-line course and is administered through an on-line platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Brown et al ( 2016 ) confirmed that, indeed, the impact of financial education on debt behavior of young people depends on the educational content: numerical and strictly financial content has a positive influence on this behavior, and more general economic content leads to worse behavior. In turn, Brugiavini et al ( 2018 ) showed that most financial education programs do not involve any subsequent evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brown et al ( 2016 ) confirmed that, indeed, the impact of financial education on debt behavior of young people depends on the educational content: numerical and strictly financial content has a positive influence on this behavior, and more general economic content leads to worse behavior. In turn, Brugiavini et al ( 2018 ) showed that most financial education programs do not involve any subsequent evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The project was promoted as part of the strategy to increase financial literacy among vulnerable groups in the population. While many financial education programs are addressed to young people (Romagnoli and Trifilidis, 2013;Bruhn et al, 2016;Brugiavini et al, 2018;Frisancho, 2018), and more recently also to women (Attanasio et al, 2019), very little has been done targeting the elderly population. However, targeting this group is particularly important for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…While the impact of an intervention on financial literacy is of common interest, confidence and overconfidence also constitute important aspects (Brugiavini et al, 2018). In particular, evidence shows that lower financial inclusion is associated with a lower level of self-assessed financial literacy (lower investments, lower access to debt, and lower appeal for pension plans; see Di Salvatore et al (2018)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly Dick and Jaroszek (2019) find low financial literacy and cognitive reflection skills are linked to high overdraft consumer credit in Germany and a large literature has found a link between financial literacy and better financial outcomes such financial risk taking, portfolio diversification, and stock market participation(Guiso and Jappelli, 2008;Bucher-Koenen and Lusardi, 2011;van Rooij et al, 2011;Lührmann, Serra-Garcia, and Winter, 2015;Von Gaudecker, 2015;and Brugiavini et al, 2018).Electronic copy available at: https://ssrn.com/abstract=3469571…”
mentioning
confidence: 99%